Vedações verticais e suas interfaces no sistema construtivo de edificações - Cardoso, Daniel Luis Antonio (2007)
The development of a greater number of projects, besides those traditionally elaborated (foundations, architecture, structure, electrical and sanitary-hydraulic installations), have made the constructive process more complex, demanding the participation of several professionals around the projects of edification to discuss and make compatible the present solutions in the interfaces between the subsystems. Construction companies, which invest in the improvement in the projects quality of their edifications tend to increase better results as to their competitiveness in the market, guaranteeing significant efficiency to the whole enterprise cycle and generating higher rationalization for the production process of their buildings. In that sense, the activities referring to the project and to the production of an edification need to be thought in an integrated way. Because there are several the interferences between the vertical sealings and the rest of subsystems of the building that interact with it, the project elaboration of vertical sealings stands out as the instrument for the compatibility of projects, because it has the property to furnish constructive details that present efficiency and constructively to the services made at the construction site. Despite the importance of project-production integration, it can be perceived a certain precariousness in the definitions of interference of the vertical sealings with the rest of the subsystems, reflection of incomplete or indefiniteness projects, leaving to the construction site the need of adaptations. Thus, through bibliographic review and case study in three building sites of a small size incorporater-constructor, the solutions adopted in the sealing masonry interface and in some subsystems are verified.